Functional Photoacoustic Imaging of Gastric Acid Secretion Using pH-responsive Polyaniline Nanoprobes - Li, Junwei (Small, 2016)
A stomach functional imaging technique based on photoacoustics presented here achieves non-invasive gastric acid secretory assessment utilizing pH-responsive polyaniline nanoprobes. A testing protocol mimicking clinical practice is established using a mouse model. After imaging, the nanoprobes are excreted outside the body without inducing systematic toxicity. Further optimization and translation of this technology can help alleviate patients’ suffering and side effects.